Efforts to Overcome the Crime of Fishing Ship Shipping in the Police Area of the Water Police Unit (Polair) of the Gorontalo Regional Police - Siti Noor Anizha (Universitas Negeri Gorontalo, 2023)
This study aims to find out what factors led to the crime of fishing boat shipping without a permit in the police area of the Gorontalo Regional Police Water Police Unit (Polair) and how to deal with the crime of fishing boat shipping in the Police area of the Gorontalo Police Water Police Unit (Polair) . This research is an empirical juridical research which in other words is a sociological research type and can also be called a field research that examines the applicable legal provisions and what happens in reality in society. Based on the results of the study, shipping crimes that occurred in the Polairud Polda Gorontalo area generally arise and develop from several factors that cohere and affect one another, such as environmental factors and low awareness of laws and regulations in shipping crimes . In several laws and regulations as contained in Law Number 2 of 2002 concerning the Indonesian National Police that there are efforts made by the Police of the Gorontalo Police Water Police Unit (Polair), including ; preventive and repressive measures.